CSIG-08. DYNAMICS OF GLIOMA GROWTH: SELF-ORGANIZATION GUIDES THE PATTERNING OF THE EXTRACELLULAR MATRIX AND REGULATES TUMOR PROGRESSION. (5th November 2018) - Comba, Andrea; B Zamler, Daniel; Dunn, Patrick; Argento, Anna; Kadiyala, Padma; Nand Yadav, Viveka; Kahana, Alon; E Kish, Phillip; Nunez, Felipe; Koschmann, Carl; Kamran, Neha; Motsch, Sebastien; et al.
Abstract: GBM remains the deadliest primary malignant brain tumor. Given the importance of invading cells, less attention has been paid to the tumor mass, even if such a mass eventually kills the patient. We previously demonstrated that human and mouse transplantable or GEMM gliomas display regular anatomical multicellular structures containing elongated cells which we named 'oncostreams'. Oncostreams are 10–20 cells wide, 2–400 um long, and are distributed throughout the tumors. Furthermore, we uncovered a negative correlation between oncostream density and animal survival suggesting that oncostreams play a role in tumor malignancy. Further data indicate that oncostreams aid local invasion of normal brain. Co-implantation experiments demonstrated that oncostreams facilitate the intratumoral spread of slow migrating cells. To determine a possible molecular distinctiveness of oncostreams we used laser capture microdissection followed by RNA-Seq, bioinformatics and network analysis. Evaluation of the transcriptome demonstrated differential expression (DE) of genes between oncostreams and adjacent tumor. Functional enrichment of DE genes showed that "collagen catabolic processes", "positive regulation of cell migration", and "extracellular matrix organization" were the most over-represented gene ontologies. Network analysis indicated that Col1a1, ACTA2, MMP9, MMP10 and ADAMTS2, genes important for cell migration and ECM interactions, are part of these networks. IHC and PCR were used to validate RNA-Seq expression changes. To understand the cellular dynamics in our system we used time lapse imagining and evaluated the results using high level statistical analyses. The following tests, i.e., velocity distribution, pair-wise correlation of local position, velocity correlation, etc. were used to characterize the dynamics of cellular intratumoral motility. These data demonstrate the existence of collective motion within glioma tumors. Taken together, our results show that oncostreams, move by collective motion, are anatomically and molecularly distinct, reveal the existence of glioma self-organization, and regulate glioma growth and invasion. Targeting oncostreams is a candidate therapeutic strategy.